(untitled) (International Educators Conference, 2025)
As advancements in oncology have dramatically improved patient survival rates, quality of life (QoL) has emerged as a critical concern for patients, particularly for younger women facing reproductive challenges. Aggressive treatments such as chemotherapy and radiation therapy may lead to fertility loss, adversely affecting life satisfaction. Fertility preservation programs are gaining prominence as essential components of treatment, offering women the opportunity to retain their reproductive functions and enhance their quality of life.